Health Behavior in School-Aged Children: Summary of the 2013/2014 WHO Survey - Shanmuganandapala, Babitha (INYI Journal, 2020)
The following piece summarizes the key findings of the 2013/2014 Health Behavior in School-Aged Children report 'Growing up unequal: gender and socioeconomic differences in young people's health and well-being'.